Oil production increase in unstable gas lift systems through nonlinear model predictive control. (September 2018) - Diehl, Fabio C.; Almeida, Cristina S.; Anzai, Thiago K.; Gerevini, Giovani; Neto, Saul S.; Von Meien, Oscar F.; Campos, Mario C.M.M.; Farenzena, Marcelo; Trierweiler, Jorge O.
Abstract: Oil production employing gas lift techniques enable the production of no natural flow wells and supply the energy lost in the reservoir caused by the field depletion, keeping the production in brown fields feasible. The multiphase flow conditions and the long pipes used to transport the fluids from the reservoir to the surface facilities, especially in deep and ultra-deepwater cases, may create unstable flow situations. Several publications in process control have discussed this problem since the 1980s, but the potential multivariable actions on the choke valve and gas lift flow have not been explored so far. In this paper the operating oil production system is treated through a nonlinear predictive control strategy. The strategy evaluation in a rigorous model (OLGA) shows the association between predictive capability and the integrated actuation in the manipulated variables results in an oil production increase and a partial or entire suppression of the instabilities in the multiphase flow. Furthermore, the rate of acting required on the valves is lower in the multivariable approach, allowing the use of slow choke valves as a final control element.